Outcomes of Intramedullary Nail Without Locking in Patients Aged 10-16 Years Having Closed Femoral Shaft Fracture - Amin, Fazal; Khan, Muhammad Dayan; Hassan, Tahir; Ahmad, Muhammad Saeed; Khattak, Muhammad Ihtisham; Haq, Abrar Ul (Biological and Clinical Sciences Research Journal, 2025)
Femoral shaft fractures in school-aged children and adolescents pose therapeutic challenges due to growth considerations and the need for early mobilization. Flexible intramedullary nailing without locking has emerged as a minimally invasive option with favorable outcomes. Objective: To assess the functional outcomes of intramedullary nail without locking in patients aged 10-16 years having closed femoral shaft fractures. Methodology: This study was conducted on a cohort of 70 patients aged 10 to 16 years presenting with closed femoral shaft fractures from August 2024 to August 2025 at the Department of Orthopedic Surgery, Hayatabad Medical Complex, Peshawar. All patients underwent closed reduction and internal fixation with a flexible intramedullary nail system without interlocking screws. Functional outcome was assessed at three-month follow-up using Flynn's TEN criteria, which categorise outcomes as excellent, good, and fair. SPSS 25 was used for analysis. Results: The mean age of 70 patients was 12.74 years. The majority of the patients were male, 64.3%. Functional outcomes were excellent in 46 cases (65.7%), good in 19 cases (27.1%), and fair in 5 cases (7.1%). Postoperative complications were skin irritation (4.3%) and limb length discrepancy (2.9%). A statistically significant association was found between functional outcome and complication status. Conclusion: Non-locking intramedullary nailing is an effective and safe surgical procedure for closed femoral shaft fractures in children aged 10–16 years. The procedure exhibited a high rate of excellent functional outcomes and a lower incidence of complications.